2017
DOI: 10.25019/mdke/5.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Bonds in Developing Countries. Case Study: Municipality of Stip, Republic of Macedonia

Abstract: The developing countries, especially in the Balkans, barely use the municipal bonds as an alternative way of financing their activities. This paper is part of the project "The municipal bonds as an alternative source of financing municipals activities and the effective management of funds, with a special emphasis to the Municipality of Stip, R. Macedonia". The paper has an important impact, according to both academic and practical perspective. It combines the experts' academic analysis with the municipals pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Currently, the US has a bond market the size of $3 trillion per annum (Brancaccio, Li, and Schürhoff 2020). Cities have preferred municipal bonds to reduce the cost of financing (reduction in the interest rate) compared to a loan from a commercial bank (Samonikov et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently, the US has a bond market the size of $3 trillion per annum (Brancaccio, Li, and Schürhoff 2020). Cities have preferred municipal bonds to reduce the cost of financing (reduction in the interest rate) compared to a loan from a commercial bank (Samonikov et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, related to where the research took place. Research conducted by Suriadi et al (2020); Al Ajlouni & Al Habeeb (2021); Surachman & Setiawan (2016); Manyanja & Manyengo (2022); Samonikov et al (2017); Gorelick (2018); as well as Nallathiga (2015) were taken place outside West Java and some others were overseas such as West Nusa Tenggara, DKI Jakarta, Saudi Arabia, Uganda, Republic of Macedonia, Africa, and India. This study chose the province of West Java as the place to do the research.…”
Section: Introductionmentioning
confidence: 99%
“…Using classical SWOT analysis and statistical analysis, they examined and found that municipal bonds as an alternative source for financing municipal activities are justified, especially if the funds are related to a particular type of revenue-generating project (Gogova Samonikov, Veselinova, Gruevski, Fotov, & Binovski, 2017). Similarly, the government of India sought to provide and finance municipal infrastructure due to the rapid urbanization process.…”
Section: Introductionmentioning
confidence: 99%